Desain Strategi Pembelajaran Maharah Al Kalam wa Al Kitabah Berbasis Promosi Produk Di Era Modern - Mohammad Sofi Anwar (Jurnal Ilmiah Iqra', 2023)
This Study aims to describe the design of maharah al kalam wal kitabah learning strategy based on product promotion using the Canva application. This is done because many young people like online business and offer their products on social media such as whatsapp, facebook, and instagram. This strategy is expected to be one of the innovations in learning Arabic for students and students who like the business world. They are expected to be able to promote their products (especially domestic products) to the international world in Arabic. For this reason, the method used in this study is a qualitative type of library research. The results of this study show the steps of using the Canva application in learning maharah al kitabah based on product promotion. After that, students are asked to demonstrate their products orally in Arabic through social media such as YouTube, Instagram, Facebook, and so on